9-10 JASAR FUTBOLSHÍLARDÍŃ OQÍW-SHÍNÍǴÍW JUMÍSLARÍN SPORT MEKTEPLERINDE MUWAPÍQLASTÍRÍP ALÍP BARÍW - Jumaniyazov, Q.T.; Utegenov, M.B. (SCIENCE and SOCIETY, 2023)
The article deals with the optimization of training process of young football players on the preparation stoge.